2017
DOI: 10.13075/mp.5893.00575
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria contamination of touch surfaces in polish hospital wards

Abstract: Background: The objective of the study has been to evaluate the pathogenic bacteria contamination of touch surfaces in hospital wards. Material and Methods: Samples were taken from frequently touched surfaces in the hospital environment in 13 units of various types. Culturing was carried out on solid blood agar and in growth broth (tryptic soy broth -TSB). Species identification was performed using the analytical profile index (API) biochemical testing and confirmed with matrix assisted laser desorption ioniza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 27 publications
3
10
1
1
Order By: Relevance
“…Multibacterial contamination of the environmental samples was estimated to be 11% [15]. This agrees with this study (7% polymicrobial).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Multibacterial contamination of the environmental samples was estimated to be 11% [15]. This agrees with this study (7% polymicrobial).…”
Section: Discussionsupporting
confidence: 90%
“…Pathogenic species—representing indicator organisms of efficiency of hospital cleaning—was demonstrated by 21.4% of samples; among them, Acinetobacter spp., Enterococcus spp., and Staphylococcus aureus were identified. Coagulase-negative staphylococci (CNS) were predominant [15].…”
Section: Discussionmentioning
confidence: 99%
“…Failure to comply with the precautions requirements, including hand hygiene, can result in the transmission of pathogens and also the contamination of the touch surfaces of hospital wards. The presence of microorganisms causing HAIs on the touch surfaces in patient zones has been confirmed in numerous studies, including Polish studies [6,7]. The traditional and modern methods of cleaning and disinfection serve to ensure a satisfactory level of hygiene in the hospital environment [6,8].…”
Section: Introductionmentioning
confidence: 99%
“…It also means that more than half of patients may have been exposed to the transmission of infection during aseptic tasks. Różańska et al [ 16 ] demonstrated that hospital surfaces can be heavily colonized with microorganisms, and contact of HCWs’ hands with these surfaces results in their contamination and, consequently, the possibility of transferring microorganisms to the patient. However, HH only may be insufficient; for example, it has been shown that drying after washing hands is a necessary phase in pre-operative preparation.…”
Section: Discussionmentioning
confidence: 99%